SYN1lIESISOF 3-HYDROxy-3’ ,4’-MElHYLENEDIOXy- 6" ,6" -DIMETHYLPYRANO (2",3":7 ,8) FLAVONE: Short Communication - Hossain, M Amzad (Biological Sciences - PJSIR, 2001)
recorded on LKB 4053, England spectrophotometer Ultrospeck in methanol (Arnax in nm). TLC performed using silica gel 60G. Mass spectra were recorded on VG 7070E analytical mass spectrometer. Elemental analyses were also obtained for all the compounds.